Health Information literacy among children at Reading Communities in Sumedang Regency - Dida, Susanne; Lusiana, Elnovani; Dewi, Retasari; Rukmana, Evi Nursanti; Safi, Abdul Qayoum (Universitas Padjadjaran, 2024)
Children are susceptible to disease due to unhealthy lifestyle habits. Hence, children need correct health information for healthy living behavior. The Reading Community (RC), as a repository and manager of knowledge, has health information services for children. Three Reading Communities (RCs) in Sumedang Regency provide health-themed books and provide health-themed literacy activities. This study aimed to determine health information literacy in children at Reading Communities in Sumedang Regency. This study used a qualitative descriptive method and was conducted at three (3) Reading Communities in Sumedang Regency, including Lingkaran Cahaya RC, Bina Kreasi Muda RC, and Pabukon Ngadongeng RC. Study results showed that children from RCs already knew the need for health information; however, they did not know the correct process for implementing it. The three RCs had various health readings, such as books, comics, and magazines. In addition, they had different strategies for planning health information for children, and they held activities according to the competencies or interests of the users. Three RCs collected health information from reading and activity-based collaboration had reading comprehension activities as an evaluation process in health information literacy and conducted reviews of activities or discussions from reading results in the form of read-aloud and think-aloud. Two RCs stored information in master books and catalogs and promoted health information activities using social media. Despite limitations in providing access to health information, the three Reading Communities have innovations in health information practices in the form of literacy activities.